Geoambiental characteristics of the Igarapé água boa do bom intento, Boa Vista, Roraima - Amorim, John Eric Lemos (Geosaberes; Vol 9 No 17 (2018): Jan - Apr, 2017)
Roraima presents a diversity of landscapes, establishing distinct phytophysiognomies such as forests, campinas-campinaranas and savannas, which constitutes the largest area of natural fields of the Amazon. The study of factors that causes disruption to the aquatic environment are fundamental for discussions and actions related to its conservation. The objective of this work is to do a research about the geoenvironmental factors that inflict directly to the water from the Igarapé Água Boa do Bom Intento. The geoenvironmental characteristics show that the Igarapé basin presents four types of soils, predominating the Yellow Argisol and the Yellow Latosol with a small spot of Argisol and Fluid Neosols, are fragile soils and poor chemically. The relief is flat to slightly undulating with the presence of lakes in times of greater intensity of rains. The climate is tropical Awi type monsoon, with high average annual temperatures of 26ºC and sharp dry season with peak between December and March and the period of rains that between the months of April to September. The savanna system is classified in Savana Park - Sp, Graminaceous or Gramineous - Lenhosa - Sg, and others such as Mata Island.
Keywords: Cerrado; Savana; Lavrado; Amazônia.